The taxonomic revision of genus Bolanthus (Caryophyllaceae) in Türkiye - Yildizbas, Avni; Koc, Murat (Magnolia Press, 2025)
A revision of the genus Bolanthus in T & uuml;rkiye is presented. Field surveys and examination of herbarium specimens preserved at ANK, EGE, GAZI, HUB, ISTE, ISTF, ISTO, KNYA, VANF, and Bozok University Department of Biology were carried out; photographs of the type specimens kept at, E, G, K, and P herbaria were also analyzed. Descriptions, original photos, distribution map, and conservation status are provided for each taxon. The phytogeographical regions where the entire taxa are distributed were stated.
Keywords: Bolanthus; Rediscovering; Revision; Taxonomy; T & Uuml; Rkiye